2016
DOI: 10.1097/spc.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

Inspiring change: humanities and social science insights into the experience and management of breathlessness

Abstract: Purpose of reviewBreathlessness can be debilitating for those with chronic conditions, requiring continual management. Yet, the meaning of breathlessness for those who live with it is poorly understood in respect of its subjective, cultural, and experiential significance. This article discusses a number of current issues in understanding the experience of breathlessness.Recent findingsEffective communication concerning the experience of breathlessness is crucial for diagnosis, to identify appropriate treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…In their recent and extensive review of COPD self-management interventions, Jordan et al called for further qualitative work to explore barriers and facilitators to COPD self-management. 19 Qualitative research, with its focus on subjective experience, is well placed to enhance understanding of such factors, 27 and enrich guidelines to support improved practice. 28 This systematic review of qualitative research aims to provide an in-depth insight into the barriers and facilitators to self-management from the perspectives of COPD patients and practitioners involved in the care of COPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…In their recent and extensive review of COPD self-management interventions, Jordan et al called for further qualitative work to explore barriers and facilitators to COPD self-management. 19 Qualitative research, with its focus on subjective experience, is well placed to enhance understanding of such factors, 27 and enrich guidelines to support improved practice. 28 This systematic review of qualitative research aims to provide an in-depth insight into the barriers and facilitators to self-management from the perspectives of COPD patients and practitioners involved in the care of COPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical work undertaken on the project has revealed that patients and healthcare providers are often at odds in the words they use to express, define and approach breathlessness and its care, which can impact early intervention, diagnosis and treatment. 13 This disconnect may be understood as a failure to translate, here understood as an attempt to convey a term meaningfully across different linguistic, cultural or social contexts.…”
Section: Methodsmentioning
confidence: 99%
“…12 These research activities have highlighted that the significance of breath, the lungs and the body is contextual, and we need to pay attention to knowledge about how lives are lived outside the clinical context, and understand the factors that influence how people’s histories, culture and imagination influence their experience. 1316…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ], comment on the individuality of responses to breathlessness that rely on prior experiences and bodily awareness (interoception). Context and culture play an important role in shaping the understanding and perception of breathlessness [ 2 4 , 6 ]. For example, among African American communities across the USA, the last words of Eric Garner, “I can't breathe”, as he suffocated in a tussle with police officers, have become a slogan for the Black Lives Matter movement and a metaphor for the lives of those living under other kinds of oppression [ 2 ].…”
mentioning
confidence: 99%
“…In view of the highly contextualised experience of breathlessness, it is critical to think about whose views are part of the debate. Discussions with experts by experience and first-person reports of experiences of breathlessness [ 3 , 5 ] have revealed how powerful language and context are in determining how people with breathlessness think about and experience their problem [ 4 , 6 ], and how this influences what they might do. Words such as “pulmonary” and “rehabilitation”, for example, may negatively impact upon the uptake of one of the most effective interventions for breathlessness [ 6 ].…”
mentioning
confidence: 99%